Promovendo a cidadania em estádio de futebol: estudo de bilheteria acessível (Ergodesign & HCI, 2014)
RESUMO Estádios esportivos são espaços públicos de lazer e cultura. Garantir amplo acesso a estes espaços, é promover cidadania e inclusão. Este artigo apresenta uma proposta de bilheteria acessível e diretrizes projetuais para futuros projetos de bilheterias, desenvolvida a partir da avaliação das condições de acessibilidade do estádio Orlando Scarpelli. Acessibilidade Espacial, Bilheteria, Pessoas com deficiência   TITLE: Promoting citizenship in soccer stadium: study of accessible ticket office ABSTRACT 1Context  The  name  "World  Cup"  denounces  the  intercontinental  coverage  of  the  event.  This demonstrates  the  importance  of  access  and  unrestricted  participation  of  all  individuals, regardless of their abilities or limitations. Focused on the analysis and qualification of accessibility at the ticket office of soccer stadiums, this article comes from a larger survey, conducted between March and June 2013, in Orlando Scarpelli Stadium, headquarters of Figueirense FC, eldest of Florianopolis, opened in 1960. With a  service capacity  for 19.584 people, the stadium  is  located  in  a predominantly residential  neighborhood,  with  non-compatible  access  roads  to  the  presence  of  an equipment of such importance. Excluding the external accesses, government's responsibility, the stadium sidewalk and the ticket office make up the first access door of the public to the games, justifying the choice of theme of this article. In  the  study  are  presented  not  only  the  problems  encountered,  but  design  solutions and  guidelines  for  accessible  ticket  office,  taking  into  account  the  public`s  needs  of Orlando Scarpelli and contributing to future projects of this nature.  2 Method The   methodological   approach   adopted   was   the   multimethods   application   that mutually  complemented  each  other,  as:  bibliographic  and  documentary  research, exploratory  visits  with  dimensional  architectural  and  photographic  surveys,  semi-structured interview and accompanied walks. The   bibliographic   research   provides   a   view   expansion   of   current   concepts   of accessibility   and   inclusion,   supporting   the   implementation   of   the   procedures performed in the study.  Among the main concepts used, it should be highlighted the understanding of spatial  accessibility, the components and the understanding of what is disability and restriction. Spatial accessibility, according to Dischinger, Bins Ely and Piardi (2012) is more than be  able  to  achieve  a  desired  place,  presupposes  the  individual's  participation  in  the activities  that  occurs  in  space,  with  safety,  comfort  and  independence.  I this  same work, the authors also define the components of  accessibility, as:  spatial orientation, communication,   displacement   and   use,   as   well   as   the   concept   of   restriction, characterized as the product of the relationship between the physiological condition of the individual and the environment in which it establishes. Eugenia   Favero   (2004)   describes   disability   as   a   significant   limitation   of   the individual,  that  cannot  be  confused  with  incapacity.  In others words, disability  is  an intrinsic characteristic of the person, that comes up when she faces or not difficulties in the experience the environment and their activities. The  interviews  aimed  to  obtain  information  about  the  measures  already  adopted,  as well  as  the  foreseen,  associated  to  accessibility  in  Orlando  Scarpelli  soccer  stadium. The attention was drawn, in particular, to those relating to the purchase of tickets. For this, we interviewed two users and a representative of the Club. According to Bins Ely et al. (2002), the Accompanied Walk consist of visits realized by researchers at the study site, in companion of a guest with a disability or with any relevant characteristic for  research.  The trajectory that  both  will  range  is  previously defined. The  activities pertinent to user participation are supervised  by  staff, without driving  or  help  the  guest,  aiming  to  gain  knowledge  about  the  way  in  which  it appropriates  of  the  space  and  it  participates.  Two  tours  were  conducted,  with  guests from different profiles, on days and times when there were no games. 3 Results Overlapping the methods, the results emerged were synthesized, following the organizational  basis  of  the  classification  of  the  accessibility  components  (DISCHINGER, BINS  ELY  and  PIARDI,  2012).  The  positive  aspects,  relating  to the  spatial  orientation  component,  were:  the  club  identification  and  the  sectors  indication,  through  its coat of arms and large dimensions signboards at strategic points. The negative aspects found,  also  were  correlated  to  components  and  motivated  the  formulation  of  proposals. Concerning the spatial orientation, the main problems were: text in hollow letters and low  contrast  against  the  background,  lack  of  preferential  attendance  indication, absence  of  tactile  floor,  visual  signaling  steps  and  tactile  maps  or  mockup  with description of the spaces. Related to communication, the greatest difficulties raised were: the small opening of ticket  office  window,  deployed  in  places  where  sunshine  can  encumber  lip-reading; inexistence of assistive technology and / or signs language interpreter, embossed text/ Braille and visual and tactile information on matches. Regarding  to  displacement,  guardrails  that prevent wheelchair’s maneuvers, floors irregularities, unevenness between floor and ticket office, no approaching area near to the  ticket  office  window,  and  waiting queue  that  cause  obstructions  in  circulations, are relevant negative aspects. Finally,  apropos  of  use,  the  negative  points  that  most  stood  out  were:  the  height  of ticket office window  -  inadequate  for people  in wheelchairs or short stature, absence of  preferential  attendance  and  no  approaching  area  near  to the  ticket  office  window. The latter problem, beyond to affecting the movement, also affect use. From  research  to  improve  the  accessibility  conditions  at  the  ticket  office  stadium,  a study of accessible ticket office had been elaborated. The proposition is constituted by 15 indications  by  specification or projective directions, related to the spatial  accessibility components (DISCHINGER, ELY and PIARDI BINS, 2012), as exposed in this article.  These  statements  relate  to:  the  visual  identity  of  the  club  and  its  signaling, actions related to the facilitation of  spatial orientation  for people with different abilities  and  limitations,  improvement  of  communication  capabilities  and  benefactors connected to displacement and safe use. Each item is presented in the text and images related  to the  project.  The  relation  between  the  parties  is  strongly  reinforced  by  presenting an overall project picture, summarizing the proposal and relating the different aspects in a corresponding table. 4 Conclusions  The Orlando Scarpelli Stadium, quite old, its project wasn't designed according to the current view of accessibility. Although the specific reforms in this direction have been observed,  the  stadium  is  in  need  of  a  global  intervention  that  ensure  the  comprehensive public’s participation. The  focus  of  accessibility  is  social  inclusion.  Which  depends  of  complex  factors: cultural,  socioeconomic  and  political  aspects.  Is  linked  to  access  to  information  and the  movement of come and go, once, allows the access and effective participation of the  individual  in  the  environment,  enables  social  interaction  and,  consequently, citizenship. This article  fetched to apply the theoretical knowledge to  projetual practice, since  its conception, permeating the whole process that led to the solutions presented. Aims to correct   the   problems   raised   by   answering   the   needs   of:   spatial   orientation, communication,  displacement  and  use-  spatial  accessibility  components –  of  ticket office in soccer stadiums. The solutions search prioritized comfort, independence and security  in  order  to  guarantee  citizenship,  since  the  "absence  of  spatial  accessibility makes   impracticable   the   effective   implementation   of   inclusion." (BINS   ELY; DISCHINGER, 2001, p. 10).The discussion of ways that promote accessibility, particularly about the soccer stadiums ticket office, does not end with the study and the solutions proposed in this article. This work points out gaps to be deepened  in  future studies,  such as  legal  issues. Although,  many  aspects  of  the  current  regulations,  NBR9050  /  2004  is  correct,  falls short in so many others. Analyzed in the light of the knowledge acquired in this study, Article  9,  correspondent  to  ticket  office,  needs  more  specifications  of  prescriptive character, aiming to qualify these spaces. To conclude, we also  make suggestions on improving  this  topic,  which  is  one  of  the  legal  aspects that require  attention  and  can help  to  further  citizenship  in  the  celebration  and  participation  in  sport.  As  shown  by Milton  Santos:  "Citizenship  is  a  law  of  society  that,  without  any  discrimination,  affects everyone (SANTOS, 1983, p.7 and 8). For the author, there  is  no effective citizenship if accessibility does not exist or is limited.  Space Accessibility, Ticket Office, People with disabilities